The correlation between serum 25-hydroxy-vitamin D levels and anti-SARS-CoV-2 S-RBD IgG and neutralizing antibody levels among cancer patients receiving COVID-19 vaccines - Rachman, Andhika; Iriani, Anggraini; Priantono, Dimas; Rumondor, Bayu Bijaksana; Betsy, Rachelle; Juanputra, Samuel (Frontiers in Nutrition, 2022)
Introduction: During the coronavirus disease 2019 (COVID-19) pandemic, vitamin D has been established as an immune-modulator that reduces pro-inflammatory damage which effectively diminish the severity of COVID-19. Vitamin D also has a significant effect against influenza and dengue and increase the seroconversion following influenza vaccination. To date, the role of vitamin D in optimizing the efficacy of COVID-19 vaccines remains unclear. This study aimed to analyze the correlation between serum 25-hydroxy-cholecalciferol or 25(OH)D levels and anti-SARS-CoV-2 S-RBD IgG and neutralizing antibody levels among cancer patients. Methodology: A multicenter cross-sectional study was conducted among solid and hematologic cancer patients who were vaccinated with two doses of the same types of COVID-19 vaccines (either mRNA, non-replicating viral vector, or inactivated) within 6 months. Result: The median serum 25(OH)D level in 119 cancer patients was 36.36 [IQR= 30.30] ng/mL. The seropositivity of S-RBD IgG and NAb reached 93.3% and 94.1%, respectively. The S-RBD IgG level was significantly higher in the sufficient group (median= 414.07 [1441.83] AU/mL) than in the deficient group (median= 91.56 [652.00] AU/mL) (p-value= 0.049). Among non-chemotherapy subjects, the anti-SARS-CoV-2 S-RBD IgG levels had a significant positive correlation with 25(OH)D levels (p-value= 0.03; R= 0.588). The NAb levels also showed significantly positive correlation with 25(OH)D level (p-value= 0.005; R= 0.561). The 25(OH)D levels were positively correlated with S-RBD IgG levels among subjects younger than 60 years old (p-value= 0.047; R= 0.136). However, serum 25 (OH)D levels showed no such correlation with S-RBD IgG levels among subjects older than 60 years old (p-value= 0.933; R= 0.136). Conclusion: Both anti-SARS-CoV-2 S-RBD IgG and NAb levels developed moderate correlation with 25(OH)D levels among subjects treated without chemotherapy. The S-RBD IgG levels also had positive correlation with 25(OH)D levels among subjects younger than 60 years old. Thus, we recommended cancer patients to maintain serum 25(OH)D levels above 30 ng/mL (75 nmol/L) to enhance the efficacy of COVID-19 vaccines.